CARIES EXPERIENCE AND ORAL HEALTH BEHAVIOURS IN ROMANIAN YOUNG ADULTS - Ruxandra Sava-Rosianu; Antonia Ilin; Octavia Balean; Simona Olariu Posiar; Alexandru Simerea; Daniela Jumanca; Atena Galuscan; Ramona Dumitrescu (Romanian Journal of Oral Rehabilitation)
Aim of the study The aim of the present study is to determine caries experience and caries prevalence in association with possible predictors in a group of students with different background. Materials and methods Participants within the study were recruited after preregistering for the event online from all the universities in Timisoara.They were asked to answer a questionnaire after signing informed consent. The questionnaire was previously pretested on a group of representative patients having similar characteristics like the study group and contained 48 closed-ended questions regarding socio-demographic parameters. oral hygiene behaviour. oral health and dietary behaviour as well as oral health literacy. Caries lesions were determined using the ICDAS system. Descriptive statistics and correlations between variables were performed using MedCalc software 2025. Results The patients’ ages ranged from 18 to 29 years. with a mean age of 21.3 years (±2.5). 66.7% females and 33.3% males. Almost 70% of the patients reported visiting the dentist regularly (once or twice per year). 14.4% reported going more than three times. and 17.8% never go. The primary reasons for the lack of dental check-ups were no complaints. high costs. and dental fear. The mean number of caries lesions on molars (2.67 ± 0.52) was higher than the restaurations (2.40 ± 0.19). with a mean difference of 0.3. The t-test revealed statistically significant differences for both caries lesions and restorations. indicating that molars are significantly more affected by untreated caries and undergo less restorative interventions. A negative partial correlation was observed between caries lesions and the frequency of dental check-ups (r = -0.48. p < 0.05) suggesting that regular dental visits are linked to fewer caries lesions. Similarly. the use of fluoridated toothpaste showed a negative correlation with caries lesions (r = -0.41. p < 0.05). highlighting its protective role. Conclusions Caries prevalence is relatively high in students from the western part of Romania and correlated to the frequency of dental check-ups. number of restauration and use of fluoridated toothpaste.